(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To describe LDL-C levels and the proportion of patients with ischemic stroke achieving an LDL-C level of <1.8 mmol/L at hospital discharge at Bach Mai Hospital. Methods: This descriptive observational study, incorporating both retrospective and prospective data collection, included 502 patients with ischemic stroke treated at the Stroke Center, Bach Mai Hospital, between June 2025 and June 2026. Data on clinical characteristics, cardiovascular risk factors, National Institutes of Health Stroke Scale (NIHSS) scores, and lipid profiles at hospital discharge were collected. Results: The mean age of the study population was 62.92 ± 11.15 years, and males accounted for 75.1%. Hypertension was the most common risk factor, observed in 68.7% of patients, followed by dyslipidemia 26.7%, diabetes mellitus 22.7%, and smoking 20.5%. The mean NIHSS score on admission was 3.45 ± 3.512, with a median of 2, indicating that most patients had mild stroke severity. The mean LDL-C level at discharge was 2.66 ± 0.93 mmol/L, with a median of 2.63 mmol/L. Only 105 patients, accounting for 20.9%, achieved the LDL-C target of <1.8 mmol/L, whereas 397 patients, equivalent to 79.1%, did not reach the recommended target at discharge. The mean total cholesterol and triglyceride levels were 4.57 ± 1.17 mmol/L and 2.13 ± 1.42 mmol/L, respectively. Conclusion: The proportion of ischemic stroke patients achieving the LDL-C target of <1.8 mmol/L at discharge remained low, despite most patients having intermediate to high cardiovascular risk. These findings highlight the need for more active lipid-lowering management, treatment optimization, and post-discharge follow-up counseling to improve LDL-C control and reduce the risk of recurrent stroke and cardiovascular events.